Dog Man - Pilkey, Dav, 1966-; Beard, George (Fictitious character); Hutchins, Harold (Fictitious character) (Dog Man, 2016)
George and Harold create a new comic book hero in Dog Man, a crimefighter with the head of a police dog and the body of a policeman, who faces off against his archnemesis Petey the Cat.